ESL students’ perception to academic writing and challenges faced In ODL / Sheela Paramasivam … [et al.] - Paramasivam, Sheela; Bhattacharyya, Ena; Jamil, Nur Fatima Aisya; Noor Eizamly, Nurin Uzma Eizzaty (Akademi Pengajian Bahasa, 2021)
This small-scale survey investigated ESL students’ perception to academic writing and challenges faced in Online Distance Learning (ODL) conducted during the Covid19 pandemic. The purpose of this study aims at answering two questions, namely what are the academic writing difficulties encountered by ESL learners and what aspects in academic writing do ESL Learners find challenging. Subjects were undergraduates in two universities in Malaysia- a public and private university. Students in both universities need to undertake academic writing course as partial fulfilment of their coursework. A needs analysis questionnaire was used to gather the data for this study. In addition, open-ended questionnaire and interviews on google meet was conducted with selected respondents to support the quantitative data. The findings of this study suggest that subjects in both universities tend to have similar difficulties in academic writing regardless of their previous educational contexts. The most common one is related to understanding author’s point of view and language use as well as coherence and cohesion. Others are related to finding relevant topics and sources, paraphrasing, synthesising, referencing and citations. Another conclusion which can be drawn is that students expectations of an online distance learning academic writing course differs from the conventions of academic writing and the expectations of the institution they are studying at. Students mainly viewed academic writing as a product approach as compared to a process approach advocated by their institutions. The findings also suggest that a needs-based syllabus, appropriate and effective teaching materials and resources and adequate teaching support strategies and technology are among factors that may develop students’ academic writing skills.